Improved Flux Performance in Brackish Water Reverse Osmosis Membranes by Modification with ZnO Nanoparticles and Interphase Polymerization - Jesús Álvarez-Sánchez; Germán Eduardo Dévora-Isiordia; Claudia Muro; Yedidia Villegas-Peralta; Reyna Guadalupe Sánchez-Duarte; Patricia Guadalupe Torres-Valenzuela; Sergio Pérez-Sicairos (Membranes, 2024)
With each passing year, water scarcity in the world is increasing, drying up rivers, lakes, and dams. Reverse osmosis technology is a very viable alternative which helps to reduce water shortages. One of the challenges is to make the process more efficient, and this can be achieved by improving the capacity by adapting membranes with nanomaterials in order to increase the permeate flux without exceeding the limits established in the process. In this research, brackish water membranes (BW30) were modified with ZnO nanoparticles by interphase polymerization. The modified membranes and BW30 (unmodified) were characterized by FTIR, AFM, contact angle, and micrometer. The membranes were tested in a cross-flow apparatus using 9000 ppm brackish water, and their permeate flux, salt rejection, and concentration polarization were determined. The salt rejection for the 10 mg ZnO NP membrane was 97.13 and 97.77% at 20 and 30 Hz, respectively, sufficient to generate drinking water. It obtained the best permeate flux of 12.2% compared to the BW30 membrane with 122.63 L m−2 h−1 at 6.24 MPa and 30 Hz, under these conditions, and the concentration polarization increased.